Media Game Edukasi Quizizz dalam Pembelajaran Sejarah Kebudayaan Islam Sebagai Upaya Meningkatkan Hasil Belajar Siswa - Amaliyatul Ulya; Ahmad Arifi (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2021)
History of Islamic Culture (SKI) is a subject that emphasizes the ability of students to take lessons from Islamic history by imitating figures who excel in their time and developing Islamic culture and civilization. The purpose of this study was to determine the effectiveness of the Quizizz Educational Game in improving student learning outcomes in SKI lessons at MI Al-Huda. This research is a type of field research with an experimental approach. The research subjects were class 4 students, totaling 52 students. Class IVA became the experimental class with 25 students and class IVB became the control class with 27 students. Methods of data collection using tests, interviews, observation, and documentation. The results showed that learning with the Quizizz Educational Game in class IVA was effective. The test results showed an increase in student learning outcomes in the experimental class compared to the control class. The average score increase in the experimental class was 9.83 and for the control class, it increased by 9.6. Based on statistical analysis with the t-test calculation, the significance value was 0.000 <0.05. The results of the statistical test indicate that there is a significant difference in the learning outcomes of SKI between the experimental group and the control group. This proves that the increase in student learning outcomes is influenced by the use of Quizizz Educational Games. Abstrak: Sejarah Kebudayaan Islam (SKI) merupakan mata pelajaran yang menekankan pada kemampuan peserta didik dalam mengambil hikmah pelajaran dari sejarah Islam dengan cara meneladani tokoh yang berprestasi pada masanya serta mengembangkan kebudayaan serta peradaban Islam. Tujuan penelitian ini untuk mengetahui efektivitas Game Edukasi Quizizz dalam meningkatkan hasil belajar siswa pada pelajaran SKI di MI Al-Huda. Penelitian ini termasuk jenis penelitian lapangan dengan pendekatan eksperimen. Subjek penelitianya adalah peserta didik kelas 4 yang berjumlah 52 siswa. Kelas IVA menjadi kelas eksperimen berjumlah 25 siswa dan kelas IVB menjadi kelas kontrol dengan jumlah 27 siswa. Metode pengumpulan data menggunakan tes, wawancara, observasi dan dokumentasi. Hasil penelitian menunjukkan bahwa pembelajaran dengan Game Edukasi Quizizz di kelas IVA berjalan efektif. Hasil tes memperlihatkan adanya peningkatan hasil belajar peserta didik di kelas eksperimen dibanding kelas kontrol. Rata-rata peningkatan nilai di kelas eskperimen sebesar 9,83 dan untuk kelas kontrol meningkat sebesar 9,6. Berdasarkan analisis statistik dengan perhitungan uji-t didapatkan nilai signifikansinya 0,000 < 0,05. Hasil uji statistik tersebut menunjukkan bahwa adanya perbedaan yang signifikan hasil belajar SKI antara kelompok eksperimen dan kelompok kontrol. Hal ini membuktikan bahwa peningkatan hasil belajar peserta didik dipengaruhi penggunaan Game Edukasi Quizizz.